2010
DOI: 10.1002/ppul.21228
|View full text |Cite
|
Sign up to set email alerts
|

CMV pneumonia in HIV‐infected ventilated infants

Abstract: Of the ventilated infants failing to respond to treatment, 72% had histologically confirmed CMV pneumonia, probably accounting for the high mortality in this cohort. The incidence of CMV disease in HIV infected infants being ventilated for severe pneumonia warrants that ganciclovir is used empirically until CMV disease is excluded. The role of lung biopsy in these circumstances needs to be researched.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 30 publications
1
30
0
1
Order By: Relevance
“…18 Another study examined lung tissue either by biopsy or using postmortem tissue from 25 HIV-infected infants admitted to an intensive care unit with severe hypoxia: CMV was identified in 36% of patients, another 36% had dual infection and 24% had PJP alone. 19 Others found that 74% of HIV and PJP-infected infants (diagnosed molecularly) had CMV viraemia. 15 A study comparing levels of CMV viraemia between HIV-exposed and -infected infants with and without pneumonia reported that a level greater than 4.1 log copies/ml identified infants likely to have CMV infection.…”
Section: The Revised Who Classification and Treatment Of Pneumonia Inmentioning
confidence: 99%
“…18 Another study examined lung tissue either by biopsy or using postmortem tissue from 25 HIV-infected infants admitted to an intensive care unit with severe hypoxia: CMV was identified in 36% of patients, another 36% had dual infection and 24% had PJP alone. 19 Others found that 74% of HIV and PJP-infected infants (diagnosed molecularly) had CMV viraemia. 15 A study comparing levels of CMV viraemia between HIV-exposed and -infected infants with and without pneumonia reported that a level greater than 4.1 log copies/ml identified infants likely to have CMV infection.…”
Section: The Revised Who Classification and Treatment Of Pneumonia Inmentioning
confidence: 99%
“…[1][2][3] Some studies report improved survival with use of the antiviral agent ganciclovir. [2,3] Despite the presence of P. jiroveci and CMV a number of other pathogens also cause and contribute to severe hypoxic pneumonia in infants. What has been missing from previous studies of severe pneumonia in HIV-infected infants, however, is a description of the host inflammatory response and cytokine/chemokine profile that accompanies this disease.…”
mentioning
confidence: 99%
“…[10] Cytomegalovirus (CMV) is now recognised as an important copathogen of severe pneumonia in infants and may be the organism driving mortality in this form of pneumonia. [1][2][3] Treatment of this form of severe pneumonia with a combination of TMP-SMX and antiviral agents has had mixed success. [1][2][3] Some studies report improved survival with use of the antiviral agent ganciclovir.…”
mentioning
confidence: 99%
See 2 more Smart Citations